A Student Life at INTI International University Volume 1 (Coffee Table Book) - Song, Kuok Thong (INTI International University, 2022)
INTI International University has always believed in fostering within our students the kind of mind, intelligence, and character which they will value for the rest of their lives. Additionally, we strive to instill ideals such as empathy, self-improvement, and societal objectives. The moment a student enrolls at our University, their life experiences a significant turning point, entering an environment within which they will be raised to become young and responsible adults. They develop lifelong memories and experiences as they advance through their studies at INTI International University. During this time, they start to make new acquaintances, become inspired to give back to society, and begin to assume leadership roles. It's a perfect time for them to learn, while taking their interest and cultural development into consideration. In essence, this is the setting that will ultimately mould the future and broaden the minds of our students. INTI International University is a place not just to obtain a certificate, but where a person learns the tough skills of life: self-discipline, commitment, friendship, sincerity, and tenacity. Being able to enjoy the University life to its fullest, and yet continue to maintain the balance between studies and social lives is itself a skill that students learn, which will also prepare them for a life of work ahead. Without doubt, students will have wonderful memories of their time at INTI International University. I am happy to share the wonderful memories of some of our previous INTIMA Presidents here in this book. May their memories and experiences be immortalised in this book for others inspiration towards success.